Child Health and the 1988-92 Economic Crisis in Peru - Paxson, Christina; Schady, Norbert (World Bank, Washington, D.C., 2013)
The effect of economic crises on child health is a topic of great policy importance. The authors use data from the Demographic and Health Surveys (DHS) to analyze the impact of the profound 1988-92 economic crisis in Peru on infant mortality and anthropometrics. They show that there was an increase in the infant mortality rate of about 2.5 percentage points for children born in late 1989 and 1990, implying that about 17,000 more children died than would have in the absence of the crisis. The authors also present suggestive evidence that the crisis affected children's nutritional status. In 1992 children under the age of 6 who had been exposed to the crisis were shorter than same-aged children in 1996 and 2000. The authors do not have data on child height prior to the crisis, but the age profile of changes in nutritional status and the fact that the 1996 and 2000 height-for-age schedules are very similar to each other both suggest that the 1992 values represent declines from previous levels. Accounting for the precise source of the increase in infant mortality and in malnutrition is difficult, but it appears that both the decrease in household incomes and the collapse in expenditures on public health played an important role.